Islamization of modern science and its philosophy: a contemporary civilizational discourse - Ali, Muhammad Mumtaz (IIUM Press, 2016)
Dr. Mumtaz Ali’s book is a wide-ranging survey of the history and development of science. He shows the unprecedented and seminal role of the Qurʼan upon human thought and the enormous methodological debt modern Western science owes to truth-based science’s contribution to the human intellectual heritage.